Historicidad del transporte en Colombia, un proceso de transición y rupturas (Tzintzun, Revista de Estudios Históricos, 2019)
The central objective of the article is to account for the transition of transportation systems in Colombia, for this, some elements of the context in which they were introduced were incorporated, as well as certain economic transformations that propitiated it. Establishing a general panorama of transport involved, on theone hand, analyzing the economic policies that have mitigated the variations, limitations and potentialities of each medium and, on the other, taking into account a series of elements (geographical, cultural, economic) that determine its functioning at the local, regional or national level.